2020
DOI: 10.1002/hed.26441
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of exosomal circMYC in radioresistant nasopharyngeal carcinoma

Abstract: Background: The relationship between circulating exosomal circular RNA (circRNA) and prognosis of patients with nasopharyngeal carcinoma (NPC) remain unknown. This study focused on the expression of exosomal circMYC and its relationship with the recurrence and prognosis of patients with NPC. Methods: The circulating exosomes were obtained from 210 patients with NPC. Quantitative polymerase chain reaction, 5-ethynyl-2 0-deoxyuridine (EdU) staining, colony formation, and bioinformatic analysis were performed. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…Knockdown of circMYC sensitizes NPC cells to irradiation. 1 Our conclusion is that circMYC is an oncogene in NPC cells and can enhance the radiotherapy resistance of NPC cells. Circulating exosomal circMYC can be used as a potential therapeutic target for NPC.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Knockdown of circMYC sensitizes NPC cells to irradiation. 1 Our conclusion is that circMYC is an oncogene in NPC cells and can enhance the radiotherapy resistance of NPC cells. Circulating exosomal circMYC can be used as a potential therapeutic target for NPC.…”
mentioning
confidence: 78%
“…The area under the curve (AUC) was 0.945, and the sensitivity and specificity were 90.24% and 94.51%, respectively, suggesting that exosomal circMYC can be used as a biomarker for differentiating radioresistant patients from radiosensitive NPC patients. 1 Therefore, our research conclusion is that exosomal circMYC can be used for differentiating radioresistant patients from radiosensitive NPC patients. Furthermore, the role of circMYC in NPC radiotherapy tolerance was further studied.…”
mentioning
confidence: 92%
“…Some molecules originated from NPC-related exosomes have been confirmed to be radiosensitive. It has been found that CircMYC, a newly discovered circular RNA (circRNA) in the circulating exosomes of NPC patients, is radioresistant and supportive for cell proliferation, and high level of circMYC is correlated with NPC recurrence 25 . Similarly, LMP1, as a vital cancer-promoting factor, exerts its carcinogenic effect by activating the P38 MARK signal of receptor cells to stimulate radiation resistance 72 .…”
Section: Exosomes Affect Various Processes Of Npcmentioning
confidence: 99%
“…Originating from extracellular vesicles, exosomes have a unique source of cargo, capable of reproducing the molecular characteristics of parent cells in the nucleus 24 . There is growing evidence that different types of exosomes target their respective receptors to exert a variety of biological effects on NPC cell proliferation and function, resulting in promoting or suppressing the tumor growth 18 , 25 - 27 . In addition to serve as intercellular carriers for material transfer, exosomes can be utilized as biomarkers for disease diagnosis 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…
To the Editor We read with interest the paper authored by Guo et al 1 published in Head & Neck in 2020. The aim of study was assessing the diagnostic value of exosomal circMYC in recurrence and prognosis of patients with nasopharyngeal carcinoma (NPC).
…”
mentioning
confidence: 99%